BETWEEN CHALLENGE AND NARRATIVE: EXPLORING GAME PREFERENCES AMONG MEXICAN MILLENNIALS - Treviño González, Raúl Alejandro (Brazilian Creative Industries Journal, 2026)
This study explores how Mexican millennial gamers describe their videogame preferences using the MDA framework to examine different forms of aesthetic enjoyment. Semi-structured interviews were conducted with thirty millennials from Monterrey, Mexico, evenly divided by gender. The results show that both men and women engage with a standard set of game aesthetics, including challenge, narrative, community, discovery, fantasy, and submission. Still, they approach and combine them in different ways. Male participants placed particular importance on narrative in classic Japanese role-playing games and on discovery in adventure games. When they socialize, they place greater emphasis on the competitive aspect of social gaming. Female participants tended to blend aesthetic experiences, connecting narrative with discovery and fantasy with submission, and emphasizing emotional engagement, cooperative play, and relaxation. Preferences were also shaped by the era in which players grew up, especially the late 1990s, which influenced their first gaming experiences and enduring attachments. These results suggest that aesthetic enjoyment is shaped by the interaction between game design, generational context, and players’ social and experiential histories.